Pengaruh Financial Literacy terhadap Investment Decision - Rifandra Adwitiya; Abdurrahman, Abdurrahman (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
In increasingly complex information era, a good understanding of financial concepts is crucial for individuals in making the right investment decisions. The level of financial literacy possessed by investors can be one of the determining factors in investor decisions in investing. Likewise, the frequency of herding behavior and the level of overconfidence possessed by investors can also influence the quality of investment decisions chosen by investors. This study aims to examine the effect of financial literacy, herding behavior and overconfidence on investment decisions. This study used 180 respondents with a sample of people who had invested and were domiciled in Jakarta. Data processing used SmartPLS and collected data by distributing questionnaires via Google Form. The results obtained in this study are Overconfidence bias has a negative effect on Investment Decisions, Loss aversion and risk aversion have a positive effect on Investment Decision making. Loss aversion and Risk Aversion in this study do not affect investment decisions. Financial literacy is needed to improve individuals' ability to invest effectively, as well as provide recommendations for educational institutions and the government to improve financial literacy programs in the community.